2022
DOI: 10.1021/acscatal.2c04832
|View full text |Cite
|
Sign up to set email alerts
|

Rh(II)-Catalyzed Enynal Cycloisomerization for the Generation of Vinyl Carbene: Divergent Access to Polycyclic Heterocycles

Abstract: Described herein is an unprecedented example of generating the endocyclic donor–donor vinyl carbene achieved by the dirhodium­(II)-catalyzed enynal cycloisomerization. The endocyclic vinyl carbene intermediate could be trapped by a diversity of alkenes, including 1,1-disubstituted alkenes, dienes, and α-methyl styrenes, which could undergo [2 + 1], [4 + 3] cycloaddition and an unexpected formal allylation, respectively, giving spiro and fused polycyclic heterocycles. In these cascade transformations, up to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Figures 3d–f show the XPS spectrum of Co−Gs nanocomposites with Co, C and O in the composite nanomaterials. The Co 2p spectrum can be deconvoluted into peaks representing Co 0 (777.8/793.2 eV), Co 2+ (781.1/796.5 eV), and satellite peaks (786.3/802.5 eV), as shown in Figure 3d [35,36] . The high‐resolution C 1s spectrum of 0.1 M Co (Figure 3e) exhibits two independent peaks near 284.8 eV and 285.9 eV, corresponding to C−C, C−O functional groups.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figures 3d–f show the XPS spectrum of Co−Gs nanocomposites with Co, C and O in the composite nanomaterials. The Co 2p spectrum can be deconvoluted into peaks representing Co 0 (777.8/793.2 eV), Co 2+ (781.1/796.5 eV), and satellite peaks (786.3/802.5 eV), as shown in Figure 3d [35,36] . The high‐resolution C 1s spectrum of 0.1 M Co (Figure 3e) exhibits two independent peaks near 284.8 eV and 285.9 eV, corresponding to C−C, C−O functional groups.…”
Section: Resultsmentioning
confidence: 98%
“…The Co 2p spectrum can be deconvoluted into peaks representing Co 0 (777.8/793.2 eV), Co 2 + (781.1/796.5 eV), and satellite peaks (786.3/802.5 eV), as shown in Figure 3d. [35,36] The highresolution C 1s spectrum of 0.1 M Co (Figure 3e) exhibits two independent peaks near 284.8 eV and 285. 3g-i, respectively, confirming the uniform distribution of these elements in the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, detailed In 2022, they further demonstrated that the easily available benzo-enynal 19 could be catalyzed by dirhodium to generate the rare endocyclic donor-donor vinyl carbene 19-A (Scheme 7). 29 This sterically encumbered dirhodium carbene could be intercepted by a diverse range of alkenes, such as styrenes 20, dienes 22 and α-methyl styrenes 24, to give a collection of polycyclic heterocycles. Mechanistic studies revealed that the 1,1-disubstituted enynal was the prerequisite for the formation of the vinyl dirhodium carbene intermediate and the formal allylation products 25 originated from a combined C-H functionalization/Cope rearrangement 30 and subsequent 1,3-H shift which was confirmed by rigorous deuterium experiments.…”
Section: Dirhodium In Enyne and Diyne Cycloisomerizationsmentioning
confidence: 99%